1990
DOI: 10.1111/j.1476-5381.1990.tb14164.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of drugs on Sephadex‐induced eosinophilia and lung hyper‐responsiveness in the rat

Abstract: Rats given an intravenous injection of Sephadex particles (0.5 mg of G200 in 1 ml of saline) on days 0, 2 and 5 had a blood eosinophilia which was maximal on day 7. On day 7, broncho‐alveolar lavage (BAL) fluids taken from the rats contained an increased number of eosinophils and fewer mononuclear cells but there was no change in the small number of neutrophils. In addition the rats were hyper‐sensitive to the increase in resistance to artificial respiration produced by 5‐hydroxytryptamine (5‐HT), given intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
3
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 35 publications
4
23
3
1
Order By: Relevance
“…We could find no report in the literature describing peripheral eosinophilia due to Cyc-A in the rats. There were reports of other drugs such as Sephadex given by injection causing peripheral eosinophilia in rats [38]. Possibly there is a migration of eosinophils from the lung to the peripheral blood in Cyc-A-pretreated rats.…”
Section: Discussionmentioning
confidence: 99%
“…We could find no report in the literature describing peripheral eosinophilia due to Cyc-A in the rats. There were reports of other drugs such as Sephadex given by injection causing peripheral eosinophilia in rats [38]. Possibly there is a migration of eosinophils from the lung to the peripheral blood in Cyc-A-pretreated rats.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, few studies have examined the effect of P-adrenoceptor agonists on other aspects of acute-inflammation, although Spicer et al (1990) demonstrated that a number of P-adrenoceptor agonists prevent sephadex-induced blood eosinophilia in rats while subcutaneous isoprenaline also inhibited sephadex-induced eosinophil accumulation in rat lung. Furthermore, in spite of the experimental evidence, currently available P2-adrenoceptor agonists with a short duration of action, such as salbutamol, do not appear to have any significant anti-inflammatory activity in therapeutic situations such as atopic dermatitis or the late phase response in asthmatics following antigen challenge (Cockroft & Murdock, 1987;Archer & Macdonald, 1987;Green et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…or intratracheally (i.t.) 2 administered Sephadex (particles of crosslinked dextran) (8,9). Rats have an endogenous hypersensitivity to dextrans such as Sephadex, which results in an eosinophilic inflammatory response (10).…”
mentioning
confidence: 99%